Luminescent properties of ZnSxSe₍₁₋x₎ mixed crystals obtained by solid-phase synthesis and melt-growing - Galkin, S.M.; Trubaieva, O.G.; Lalayants, O.I.; Rybalka, I.A.; Shevchenko, O.A.; Bryleva, K.Yu.; Golinka-Bezshyyko, L.O. (Functional Materials, 2018)
The luminescence characteristics of ZnSxSe₍₁₋x₎ mixed crystals (MC) obtained by solid-phase synthesis and melt-growing were studied. In X-ray luminescence spectra of ZnSxSe₍₁₋x₎ powdered MC synthesized from ZnS and ZnSe powders, where x = 0.90 to 0.99, a non-elementary band with λmax ~ 520 nm (I₁) was observed, but for ZnSxSe₍₁₋x₎ with low concentrations of ZnS (x = 0.05) the luminescence band with λmax = 600-630 nm (I₂) was a dominate. In X-ray luminescence spectra of ZnSxSe₍₁₋x₎ MC (x = 0.05 to 0.3) obtained by the melt growth only I₂ luminescence band with shifted maximum from 610 nm to 590 nm at sulfur concentration increasing was observed. It is shown that for the composition of ZnS₀.₁₅Se₀.₈₅ MC annealed in zinc vapor the light yield of X-ray luminescence is 1.6 times higher than in the commercial ZnSe(Te) crystals. In consideration of this fact it might be supposed, that this MC can find application in scintillation detectors of X-ray and low-energy gamma radiation.